Appraisal of the Possible Role of PPARγ Upregulation by CLA of Probiotic Pediococcus pentosaceus GS4 in Colon Cancer Mitigation. (24th February 2023) - Dubey, Vinay; Mishra, Alok Kumar; Ghosh, Asit Ranjan
Abstract : The prevalence of colon cancer (CC) is increasing at the endemic scale, which is accompanied by subsequent morbidity and mortality. Although there have been noteworthy achievements in the therapeutic strategies in recent years, the treatment of patients with CC remains a formidable task. The current study focused on to study role of biohydrogenation-derived conjugated linoleic acid (CLA) of probiotic Pediococcus pentosaceus GS4 (CLAGS4 ) against CC, which induced peroxisome proliferator-activated receptor gamma (PPAR γ ) expression in human CC HCT-116 cells. Pre-treatment with PPAR γ antagonist bisphenol A diglycidyl ether has significantly reduced the inhibitory efficacy of enhanced cell viability of HCT-116 cells, suggesting the PPAR γ -dependent cell death. The cancer cells treated with CLA/CLAGS4 demonstrated the reduced level of Prostaglandin E2 PGE2 in association with reduced COX-2 and 5-LOX expressions. Moreover, these consequences were found to be associated with PPAR γ -dependent. Furthermore, delineation of mitochondrial dependent apoptosis with the help of molecular docking LigPlot analysis showed that CLA can bind with hexokinase-II (hHK-II) (highly expressed in cancer cells) and that this association underlies voltage dependent anionic channel to open, thereby causing mitochondrial membrane depolarization, a condition that initiates intrinsic apoptotic events. Apoptosis was further confirmed by annexin V staining and elevation of caspase 1p10 expression. Taken all together, it is deduced that, mechanistically, the upregulation of PPAR γ by CLAGS4 of P . pentosaceus GS4 can alter cancer cell metabolism in association with triggering apoptosis in CC.